2015
DOI: 10.1080/00914037.2014.996710
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Containing Bioinspired Polyurethanes: Biodegradable Medical Adhesive Materials

Abstract: Highly adhesive bioinspired polyurethanes (PUs) based on the chlorogenic acid (CLA) were prepared from 4,4 0 -methylenebis (cyclohexyl isocyanate) (MCI) and polyethylene glycol 200 (PEG 200). The polyurethanes exhibited the lowest glass transition temperature (T g ), improved thermal stability and good adhesive properties. The highest adhesion strength was found as 373.3 AE 47.5 kPa for 10% CLA containing PUs. The polyurethanes were observed to be biodegradable and were in the range of 19-24% for 8 weeks as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The authors have reported the effect of incorporation of chlorogenic acid and xylose in these polyurethanes. The xylose incorporated polymers showed stronger adhesion (94.0 ± 2.8 kPa) compared to the chlorogenic acid-incorporated polymers (40.09 ± 5.08 kPa) on soft tissue. , A bone adhesive developed by reinforcing a polyurethane matrix with nanocrystals of hydroxyapatite showed improved adhesive performance on wet bone in comparison to the commercial bone cement …”
Section: Polysaccharide Polypeptide or Polymeric Adhesivessupporting
confidence: 91%
See 1 more Smart Citation
“…The authors have reported the effect of incorporation of chlorogenic acid and xylose in these polyurethanes. The xylose incorporated polymers showed stronger adhesion (94.0 ± 2.8 kPa) compared to the chlorogenic acid-incorporated polymers (40.09 ± 5.08 kPa) on soft tissue. , A bone adhesive developed by reinforcing a polyurethane matrix with nanocrystals of hydroxyapatite showed improved adhesive performance on wet bone in comparison to the commercial bone cement …”
Section: Polysaccharide Polypeptide or Polymeric Adhesivessupporting
confidence: 91%
“…The xylose incorporated polymers showed stronger adhesion (94.0 ± 2.8 kPa) compared to the chlorogenic acid-incorporated polymers (40.09 ± 5.08 kPa) on soft tissue. 132,133 A bone adhesive developed by reinforcing a polyurethane matrix with nanocrystals of hydroxyapatite showed improved adhesive performance on wet bone in comparison to the commercial bone cement. 4 Tissue adhesives employing different techniques like laser welding, layer-by-layer assembly, and temperature-dependent hardening have also been developed.…”
Section: ■ Cyanoacrylate Gluementioning
confidence: 99%
“…26−30 In previous studies, for chlorogenic acid (CLA)-based polyurethanes, the highest adhesion values were measured as 226.6 ± 35.2 kPa and 373.3 ± 47.5 kPa for 1 and 24 h curing times in 10% of CLA containing PUs, respectively. 9 According to our adhesion test results, NPU-PEG-X-15% polymer showed higher values than CLA-based PUs.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…Surgical adhesives can be divided as biological, synthetic, semisynthetic and biomimetic. Among the synthetic or semisynthetic bioadhesives, polyurethanes have been considered as a promising adhesive material due to their biocompatibility and biodegradability properties. , UV curable polyurethane adhesive based on polycaprolactone diol and 2-isocyanatoethyl methacrylate was developed by Ferreira et al According to their results, biodegradability was around 10% after 6 weeks and material is slightly hemolytic . In the another study, Ferreira et al developed a biodegradable urethane-based bioadhesive containing free isocyanate groups.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, polyurethanes (PUs) are one of the most versatile materials and are widely used in different application such as Shape memories, coatings, adhesives, and thermoplastic elastomers . PUs generally consist of a soft segment which is formed from linear, long chain diol and hard segment built from diisocyanate and low molecular weight diol or diamine.…”
Section: Introductionmentioning
confidence: 99%